Analisis Penerapan Restorative Justice dalam Penyelesaian Kasus Kecelakaan Lalu Lintas yang Mengakibatkan Kematian (Studi Di Kepolisian Polres Pelabuhan Belawan) - Chandra Prayuda; Ridho Mubarak; Rafiqi Rafiqi (Universitas Medan Area, 2022)
The case of a traffic accident, there was no intention of the perpetrator to take this action at first, but due to negligence or lack of caution eventually resulted in the accident. Weak public awareness of traffic regulations can be seen from the low level of community discipline in driving, resulting in a culture of undisciplined society. In Law No. 22 of 2009 concerning Road Traffic and Transportation, the act can be threatened with imprisonment, but in its development the concept of restorative justice chose imprisonment as the last option, the important point being reconciliation between the two parties and the victim's family. At the level of resolving traffic accident cases, the Police in this case as investigators in the case of the accident, whether that resulted in the death of the victim, or experiencing physical disability, have tried to use mediation in resolving accident cases. The problem discussed in this thesis is regarding the application of Restorative Justice in resolving cases of traffic accidents that resulted in death in the Belawan Harbor Police area. Constraints to the application of Restorative Justice in resolving cases of traffic accidents that resulted in death in the Belawan Harbor Police Police Area. The type of research in this thesis is normative juridical, namely a research method that examines document studies, using various secondary data such as laws and regulations, court decisions, legal theory and can also be in the form of scholars' opinions. The results of this study are the application of Restorative Justice in solving traffic accident cases that result in death by emphasizing the direct participation of perpetrators, victims and the community in the process of resolving criminal cases. the concept of restorative justice is based on criticism of the implementation of the criminal justice system with imprisonment which is considered ineffective in resolving social conflicts. Constraints to the application of Restorative Justice in resolving cases of traffic accidents that result in death is the limited budget for providing optimal services to the community is an important obstacle and problem in providing traffic accident handling services. This is an obstacle in dealing with accidents in the jurisdiction of the Belawan Port Police Police.